River inputs, re‐mineralisation and the spatial and temporal distribution of inorganic nutrients in Tasman Bay, New Zealand - Lincoln Mackenzie (New Zealand Journal of Marine and Freshwater Research, 2004)
To improve understanding of the temporal and spatial variability of biological productivity relevant to fisheries enhancement within Tasman Bay, New Zealand, it is necessary to evaluate the importance of variations in river inflows on inorganic nutrient dynamics. To achieve this, a series of synoptic surveys of surface and water column salinity fields and inorganic nutrient concentrations were carried out over a 1‐year period, at seasonally representative times, during, and soon after, a range of flow regimes in the major freshwater tributaries of Tasman Bay. An assessment was made of the relative importance of external (i.e., river borne) and internal (i.e., recycling) nutrient sources that control the fertility of the Tasman Bay water column. Flood events in the bay's catchment cause significant changes in the levels of dissolved nitrogen, phosphorus, and silica in surface waters, and on an annual basis 60–70% of the input of “new” dissolved inorganic nitrogen from freshwater tributaries is contributed by the Motueka River. As a consequence there is a pronounced east to west gradient in nutrient enrichment, and oceanic water most frequently intrudes along the eastern shore. Surface salinity and inorganic nutrient distribution patterns and inferred water movements are consistent with the left hand deflection of buoyant river plumes. The predictable timing and magnitude of the winter nitrate/nitrite maxima suggests that light is the main factor limiting phytoplankton production and nutrient assimilation during the winter, and that benthic and pelagic re‐mineralisation processes are the dominant mechanism generating the annual nutrient maxima within the water column as a whole. Calculations suggest that the net accumulation of inorganic nitrogen via endogenous re‐mineralisation over the autumn‐winter period is of a similar order of magnitude to the annual introduction of new nitrogen from freshwater sources. How this compares to inputs of new nitrogen by advection from oceanic sources has yet to be determined.